Gerakan Sosial: Aksi Bela Palestina Boikot Produk Israel Di Kota Padang 2017-2023 - Rafid Sugandi; Riri Anggraini (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to describe the social movement of boycotting Israeli affiliated products and its impact in Padang City, 2017-2023. The research method used is the library study method (library research). This research uses an empathetic approach to study the phenomenon of the social movement of boycotting Israeli-affiliated products in Padang city. The results of this study show that after the British issued the